2019
DOI: 10.1111/jels.12235
|View full text |Cite
|
Sign up to set email alerts
|

Race and Class: A Randomized Experiment with Prosecutors

Abstract: Disparities in criminal justice outcomes are well known, and prior observational research has shown correlations between the race of defendants and prosecutors' decisions about how to charge and resolve cases. Yet causation is questionable: other factors, including unobserved variation in case facts, may account for some of the disparity. Disparities may also be driven by socioeconomic class differences, which are highly correlated with race. This article presents the first blinded, randomized controlled exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 1 publication
3
15
0
Order By: Relevance
“…Scientific attempts to understand the high rates of incarceration in the U.S. frequently implicate tough-on-crime policies like mandatory sentencing laws, the war on drugs, economic disparities, the privatization of prisons, and a long history of racial bias (see Travis et al, 2014 ). Less attention has been paid to the roles of prosecutors, who have wide discretion in deciding whether or not to file criminal charges, which charges are filed, and even what sentence will be considered (see Wise et al, 2009 ; Byers et al, 2012 ; Bushway et al, 2014 ; Robertson et al, 2019 ; Eck and Crabtree, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific attempts to understand the high rates of incarceration in the U.S. frequently implicate tough-on-crime policies like mandatory sentencing laws, the war on drugs, economic disparities, the privatization of prisons, and a long history of racial bias (see Travis et al, 2014 ). Less attention has been paid to the roles of prosecutors, who have wide discretion in deciding whether or not to file criminal charges, which charges are filed, and even what sentence will be considered (see Wise et al, 2009 ; Byers et al, 2012 ; Bushway et al, 2014 ; Robertson et al, 2019 ; Eck and Crabtree, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…When we raised the issue in interviews and focus groups, prosecutors denied that the race of the defendant was a factor. Previous research on the salience of race in charging decisions by Robertson et al (2019) found that the race of a defendant in a vignette was not significantly related to the severity of charging. Other studies have reported mixed results (e.g., Berk & Campbell, 1993; Starr & Rehavi, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…We do, however, conclude that prosecutors’ race is salient in their role orientations, as Black prosecutors were more often Reformers than Enforcers and thus more likely than their colleagues to consider the defendant’s background and impact of the criminal charge. Quantitative studies that examine the role of race in prosecutors’ decision-making have also found differences in case processing and outcomes between White and non-White prosecutors (LaPrade, 2020; Robertson et al, 2019). This may be because Black prosecutors are more likely to have experienced the effects of the justice system, either firsthand or vicariously.…”
Section: Discussionmentioning
confidence: 99%
“…A related limitation concerns the participation rates, which were unequally distributed-ranging from below 30% in Cook County to above 65% in Hillsborough County. It is difficult to ascertain what should be considered an acceptable rate with prosecutors when previous studies have shown both high (e.g., Frederick & Stemen, 2012: 95%) and low (e.g., Cross & Whitcomb, 2017: 3%;Robertson et al, 2019: 12%) participation rates. While there is some cause for concern regarding the overall participation rate for this study (<50%), the supplemental models we estimated (see Note 9) make clear the association between the two orientation variables and punitive attitudes held across jurisdictions with higher rates of participation as well as those with lower rates of participation.…”
Section: Limitations and Future Researchmentioning
confidence: 99%